2006
DOI: 10.1016/j.neuroimage.2005.08.065
|View full text |Cite
|
Sign up to set email alerts
|

A temporal comparison of BOLD, ASL, and NIRS hemodynamic responses to motor stimuli in adult humans

Abstract: In this study, we have preformed simultaneous near-infrared spectroscopy (NIRS) along with BOLD (blood oxygen level dependent) and ASL (arterial spin labeling)-based fMRI during an event-related motor activity in human subjects in order to compare the temporal dynamics of the hemodynamic responses recorded in each method. These measurements have allowed us to examine the validity of the biophysical models underlying each modality and, as a result, gain greater insight into the hemodynamic responses to neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
519
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 715 publications
(573 citation statements)
references
References 54 publications
29
519
3
Order By: Relevance
“…rise times for the diffusion MRI, SE-BOLD MRI, GE-BOLD MRI, and total-Hb (NIRS) responses were 1.2 ± 0.1, 3.3 ± 0.9, 4.4 ± 0.3, and 2.1±0.6 secs, respectively ( Figure 6A). The rise times of the SE-BOLD and total-hemoglobin signals were faster than those of GE-BOLD, which was in agreement with several previous works (Hulvershorn et al, 2005;Huppert et al, 2006), but were statistically significantly longer than the diffusion MRI signal. Interestingly, differences in the decay times were even larger: 2.0±0.6, 6.2±0.5, 6.4±0.4, and 6.8±0.8 secs, for the diffusion MRI, SE-BOLD MRI, GE-BOLD, and totalHb responses, respectively ( Figure 6B).…”
Section: Response Timessupporting
confidence: 92%
See 1 more Smart Citation
“…rise times for the diffusion MRI, SE-BOLD MRI, GE-BOLD MRI, and total-Hb (NIRS) responses were 1.2 ± 0.1, 3.3 ± 0.9, 4.4 ± 0.3, and 2.1±0.6 secs, respectively ( Figure 6A). The rise times of the SE-BOLD and total-hemoglobin signals were faster than those of GE-BOLD, which was in agreement with several previous works (Hulvershorn et al, 2005;Huppert et al, 2006), but were statistically significantly longer than the diffusion MRI signal. Interestingly, differences in the decay times were even larger: 2.0±0.6, 6.2±0.5, 6.4±0.4, and 6.8±0.8 secs, for the diffusion MRI, SE-BOLD MRI, GE-BOLD, and totalHb responses, respectively ( Figure 6B).…”
Section: Response Timessupporting
confidence: 92%
“…However, the assumption of a nonvascular origin of the water-diffusion signal is a subject of controversy (Jin and Kim, 2008;Miller et al, 2007;Yacoub et al, 2008). Furthermore, vascular responses that are faster than BOLD signals have also been observed through measurements of the regional cerebral blood volume (rCBV) and the total local hemoglobin content (Huppert et al, 2006;Lu et al, 2003;Malonek et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…HHb concentration increases or decreases after stimulus onset. Similar discrepancies have been described further as partial volume effect (Boas et al, 2001, Strangman et al, 2002b, Huppert et al, 2006, Xu et al, 2007. Partial volume effect is the effect wherein insufficient image resolution leads to a mixing of different tissue types.…”
Section: Partial Volume Effectsupporting
confidence: 55%
“…Perfusion fMRI has several advantages over blood oxygen level dependent (BOLD) fMRI. For instance, the signal is more directly related to neural activity, arising approximately 1-2 s earlier than the peak BOLD response (see Cavusoglu et al, 2012;Huppert et al, 2006), it provides a quantitative estimate of signal change in absolute units, and it is demonstrably less sensitive to speech-related susceptibility artifacts (Kemeny et al, 2005; for reviews, see Detre et al, 2012;Liu & Brown, 2007 Oppenheim et al, 2010), additional signal changes in the right IFG and ACC are likely to be observed (Kuhl et al, 2007;Levy & Anderson, 2008;Wimber et al, 2009). Finally, unlike previous neuroimaging studies, we included presentation cycle as a factor in our analyses.…”
Section: The Present Studymentioning
confidence: 99%